1961
DOI: 10.2307/1933497
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Competition for Food in Fish

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology. http://www.jstor.org This content downloaded from 128.235.251.160… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1966
1966
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…The acquisition of optimal feeding stations or territories is of survival benefit to individual fish. Despotic fish in hierarchies or successful territorial fish grow more rapidly than subordinates or refugees (Kalleberg 1958;McPhee 1961;Chapman 1962;Mason and Chapman 1965). Reimers (1968) found that dominance-subordination relationships among juvenile fall chinook salmon were largely determined on the basis of size, Dominant fish, in possession of the best terrritories relative to food and shelter, were the largest.…”
Section: A Summary Of Egg-to-emergent-fry Survival For Streamside Incubators In Oregon Is Shown Inmentioning
confidence: 99%
“…The acquisition of optimal feeding stations or territories is of survival benefit to individual fish. Despotic fish in hierarchies or successful territorial fish grow more rapidly than subordinates or refugees (Kalleberg 1958;McPhee 1961;Chapman 1962;Mason and Chapman 1965). Reimers (1968) found that dominance-subordination relationships among juvenile fall chinook salmon were largely determined on the basis of size, Dominant fish, in possession of the best terrritories relative to food and shelter, were the largest.…”
Section: A Summary Of Egg-to-emergent-fry Survival For Streamside Incubators In Oregon Is Shown Inmentioning
confidence: 99%
“…Aggressive behavior seems to be size dependent (Chiszar et al 1972); the largest, most dominant fish tend to have the advantage (McComish 1971;Chiszar et al 1972;Henderson and Chiszar 1977;Beacham 1987). Allee et al (1948) and MacPhee (1961) showed that within sunfish species, dominant individuals obtain more food and grow faster than subordinates. Growth variation due to social interactions may reduce overall production.…”
mentioning
confidence: 99%